Transforming Curricula in Higher Education: Description of Two Perspectives From the Global South and the Global North - Mpofu-Hamadziripi, Nomalanga; Rauch, Franz; Dulle, Mira (Frontiers in Education, 2022)
The paper is part of the broader narrative of transforming curricula in universities in Zimbabwe and Austria. The landscape in higher education globally is inexorably shifting as a result of major global forces of change. For that reason, higher education cannot remain immune to these global challenges and changes. Rather, universities should be the agents of change. Higher education in Austria and Zimbabwe, in response to these global challenges and imperatives, has begun the process of transforming curricula to educate graduates for the future. The paper explores the strategies that universities in Zimbabwe and Austria have initiated to be able to support students to make meaningful contributions to the global learning and sustainability narrative. The two central questions that this paper seeks to answer are: Which additional innovations in curricula and new epistemologies should universities in Zimbabwe and Austria implement in order to educate graduates for a sustainable future? What can universities in the South and in the North learn from each other? In attempting to reflect on these questions, pertinent lessons will be drawn from initiatives in Austria and Zimbabwe to build capacity to achieve the Education for Sustainable Development (ESD) agenda through various strategies.